A study of the arterial variations in the popliteal regions, are they symmetrical or not? - Salehuddin, Ahmad Ruzain; Buyong, Zunariah; Che Mohamed, Siti Kamariah; Hassan, Radhiana (Faculty of Medicine, International Islamic University Malaysia, 2015)
Objective: To assess the prevalence of the arterial variations in the popliteal regions and the symmetrical characteristic of the popliteal artery branching patterns in both knees of all subjects. Methodology: 77 subjects (154 knees) were prospectively studied using colour Doppler ultrasonography in this descriptive and cross-sectional study. No subject had anomalies of the lower limbs or history of previous lower limb surgery. Subjects with cardiovascular disease were excluded from this study. Results: Prevalence of the popliteal artery variations was 4.5%. The two variants (type I-B and type II-A) were seen in both knees. There were 5 subjects who had at least one variant in either side of their knees. Two subjects had type II-A occurred bilaterally in both knees while 3 other subjects had unilateral pattern of type I-B in combination with type I-A in their knees. Conclusion: Symmetrical and non-symmetrical pattern can be seen in the population depending on the popliteal artery branching pattern